Contemporary media approaches - a reading of the foundations and starting points - - Djamel KOUAICHE (Social Sciences Journal, 1970)
Media theories are the sum total of what the theorists of communication and mass media have reached, as contemporary media theories are related to media policies in society, the extent of control over the media in terms of politics, and the opportunities for censorship over it and its contents that are published or broadcast through it, to raise the question of whether the government controls the media. The media, or do they have absolute freedom to move, or adhere to the rules set by the laws in force. Especially since the group of factors that participate in establishing the logic of scientific theories in the various human and life fields, in fact, stem from the human environment and the set of stimuli and responses that are formed according to it. He was able to Man diagnoses those environmental, social and psychological factors after knowing the language and its vocabulary, because the language in its first form and its simple, primitive nature was necessary for the life of the group and a basis for the formation of relations between man and his fellow man. It made the circulation of experience possible between individuals, generations and societies. And the human language in this broad sense has become a major tool of communication between human beings, and in the second aspect it has become a tool of thought and a tool for exchanging opinions and ideas between people. It is not surprising that the media of developing countries have a say in this field, especially since they were afflicted with the conditions imposed on them by colonial policies. And what they suffer from the severity of the political differences, which were reflected as a result on their media activities. Despite the entry of the world into the twenty-first century, and the era of informatics and advanced means of communication, we notice the continuing confusion of developing countries in their information and communication problems, which have become more difficult and complex. The media remained a shadow of politics in the daily communication movement to implement the curricula political, economic, intellectual, educational, and cultural, in this or that country. And the connection of man’s awareness of these social factors and formations and his appreciation of the objective and subjective conditions that surround him, which are directly related to his national language, especially since language is the expression of our appreciation for objective reality, and awareness and language appeared in A specific stage of the social development of humanity, so that human beings can communicate and communicate with Language gives man, in addition to his biological inheritance, an opportunity for the optimal investment of culture and knowledge. Modern science has provided language with multiple possibilities and means to express the subtleties of actual rulings in their theoretical and applied forms for various human needs. There is a relationship between media theories and media philosophy. Media philosophy is the study of the dialectical relationship between media and its applications in society. That is, the analysis of the interaction between the foundations of media as a science and its actual practices in social reality. Theorists see that media theories are part of media philosophy, because media philosophy is more general and comprehensive than theories. Media theories are often used as media philosophy or media doctrines, but in reality that The use of the expression media theories was in its entirety a reflection of talking about social and economic ideologies and beliefs, or talking about the origins and sources of the media process (sender, receiver, means, etc.).